High‐Throughput Preparation of New Photoactive Nanocomposites. Issue 11 (3rd May 2016) - Conterosito, Eleonora; Benesperi, Iacopo; Toson, Valentina; Saccone, Davide; Barbero, Nadia; Palin, Luca; Barolo, Claudia; Gianotti, Valentina; Milanesio, Marco
Abstract: New low‐cost photoactive hybrid materials based on organic luminescent molecules inserted into hydrotalcite (layered double hydroxides; LDH) were produced, which exploit the high‐throughput liquid‐assisted grinding (LAG) method. These materials are conceived for applications in dye‐sensitized solar cells (DSSCs) as a co‐absorbers and in silicon photovoltaic (PV) panels to improve their efficiency as they are able to emit where PV modules show the maximum efficiency. A molecule that shows a large Stokes' shift was designed, synthesized, and intercalated into LDH. Two dyes already used in DSSCs were also intercalated to produce two new nanocomposites. LDH intercalation allows the stability of organic dyes to be improved and their direct use in polymer melt blending. The prepared nanocomposites absorb sunlight from UV to visible and emit from blue to near‐IR and thus can be exploited for light‐energy management. Finally one nanocomposite was dispersed by melt blending into a poly(methyl methacrylate)‐block‐poly( n ‐butyl acrylate) copolymer to obtain a photoactive film. Abstract : Dye harder : New low‐cost photoactive hybrid materials based on organic molecules inserted into hydrotalcite (LDH) are produced. These materials absorb below λ =400 nm and emit at approximately λ =500 nm, suitable for energy down‐shifting and light‐management applications. One nanocomposite is dispersed by melt blending into a block copolymer. In this way a photoactive film is obtained that is able to emit at which silicon photovoltaic modules show the maximum efficiency.